Effect of berberine on the viability of adipose tissue-derived mesenchymal stem cells in nutrients deficient condition. Issue 5 (4th March 2018) - Ghorbani, Ahmad; Baradaran Rahimi, Vafa; Sadeghnia, Hamid Reza; Hosseini, Azar
Abstract: This study was designed to examine whether berberine protects rat adipose tissue-derived stem cells (ASCs) against glucose and serum deprivation (GSD)-induced cell death. ASCs were cultured for 24 h in GSD condition in the presence of berberine and then cell viability, apoptosis and generation of reactive oxygen species (ROS) were evaluated. The GSD condition significantly decreased ASCs viability and increased ROS generation and apoptosis. Incubation with 0.75–3 μM berberine partially increased cell viability and decreased ROS generation and apoptosis in GSD condition. In conclusion, berberine partially protects ASCs in nutrients deficient condition and may help ASCs to preserve their survival during cell therapy of ischemia. Abstract :